A restrictive ventilatory pattern is common in patients with univentricular heart after Fontan palliation and associated with a reduced exercise capacity and quality of life. (30th October 2018) - Callegari, Alessia; Neidenbach, Rhoia; Milanesi, Ornella; Castaldi, Biagio; Christmann, Martin; Ono, Masamichi; Müller, Jan; Ewert, Peter; Hager, Alfred
Abstract: Aim: The Fontan circulation is highly dependent on ventilation, improving pulmonary blood flow and cardiac output. A reduced ventilatory function is reported in these patients. The extent of this impairment and its relation to exercise capacity and quality of life is unknown and objective of this study. Methods: This multicenter retrospective/cross‐sectional study included 232 patients (140 females, age 25.6 ± 10.8 years) after Fontan palliation (19.8% atrioventricular connection; 20.3% atriopulmonary connection; 59.9% total cavopulmonary connection). Resting spirometry, cardiopulmonary exercise tests, and quality‐of‐life assessment (SF‐36 questionnaire) were performed between 2003 and 2015. Results: Overall, mean forced expiratory volume in one second (FEV1 ) was 74.7 ± 17.8%predicted (%pred). In 59.5% of the patients, FEV1 was <80%pred., and all of these patients had FEV1 /forced vital capacity (FVC) > 80%, suggestive of a restrictive ventilatory pattern. Reduced FEV1 was associated with a reduced peakVO2 of 67.0 ± 17.6%pred. ( r = 0.43, P < .0001), even if analyzed together with possible confounding factors (sex, BMI, age, years after palliation, number of interventions, scoliosis, diaphragmatic paralysis). Synergistically to exercise capacity, FEV1 was associated to quality of life in terms of physical component summary ( r = 0.30, P = .002), physical functioning ( r = 0.25, P = .008), bodily pain ( r = 0.22, P = .02), and general health ( r = 0.16, P = .024). Lower FEV1 was associated with diaphragmatic paralysis ( P = .001), scoliosis ( P = .001), higher number of interventions ( P = .002), and lower BMI ( P = .01). No correlation was found to ventricular morphology, type of surgeries, or other perioperative/long‐term complications. Conclusions: This study shows that the common restrictive ventilatory pattern in Fontan patients is associated with lower exercise capacity and quality of life. Risk factors are diaphragmatic paralysis, scoliosis, a high total number of interventions and low BMI.